1998
DOI: 10.1088/0953-8984/10/4/013
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of thermally vacuum evaporated thin films

Abstract: Silver antimony diselenide thin films were prepared by a thermal vacuum evaporation technique onto quartz and glass substrates kept at room temperature . The as-deposited films were amorphous and transformed to a face centred cubic (FCC) polycrystalline nature with the lattice constant on post-deposition annealing above 423 K for one hour in argon atmosphere. The optical constants (the refractive index n, and the absorption index k) of the films were determined for several samples of different thickness (180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
2
13
1
1
Order By: Relevance
“…Measurement of diffuse reflectance in AgSbSe 2 and AgSbTe 2 provided the evidence of the apparent bandgap (of about 1.03 eV 6 and 0.35 eV 7 for AgSbSe 2 and AgSbTe 2 , respectively), whereas electrical conductivity measurements at room temperature 5 suggested semimetallic behavior of both compounds. de Haas-van Alphen effect measurements show that AgSbTe 2 is a semiconductor with a very narrow energy gap of approximately 7 meV, but according to the authors, it can be considered as an indirect zero-gap material above 100 K. 8 On the other hand, we have recently found that homogenous and isostructural AgSbSe 2 -AgSbTe 2 solid solutions exhibit evident semiconducting temperature dependence of electrical conductivity 9 (E g % 0.3 eV).…”
Section: Introductionmentioning
confidence: 97%
“…Measurement of diffuse reflectance in AgSbSe 2 and AgSbTe 2 provided the evidence of the apparent bandgap (of about 1.03 eV 6 and 0.35 eV 7 for AgSbSe 2 and AgSbTe 2 , respectively), whereas electrical conductivity measurements at room temperature 5 suggested semimetallic behavior of both compounds. de Haas-van Alphen effect measurements show that AgSbTe 2 is a semiconductor with a very narrow energy gap of approximately 7 meV, but according to the authors, it can be considered as an indirect zero-gap material above 100 K. 8 On the other hand, we have recently found that homogenous and isostructural AgSbSe 2 -AgSbTe 2 solid solutions exhibit evident semiconducting temperature dependence of electrical conductivity 9 (E g % 0.3 eV).…”
Section: Introductionmentioning
confidence: 97%
“…Alloys of both compounds either in single-crystal form or in thin-film form have received considerable interest owing to their optical and electronic properties. They are attractive phase-change (PC) materials used as a switching medium in rewritable optical memories [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[12] without denomination of other phases due to their large intensity. The addition of small amount of indium additive (x = 5) results in a decrease in the intensity of diffraction peaks of AgSbSe 2 without forming new phases.…”
Section: Composition and Crystalline Phasesmentioning
confidence: 99%
“…An addition of a third element usually affects the properties of chalcogenide semiconductors by creating compositional and configurational disorder in the material with respect to binary alloys [11]. Ag-Sb-Se is a narrow band gap p-type * E-mail: prafiziks@gmail.com semiconducting system which crystallizes to AgSbSe 2 with a cubic NaCl type structure [12]. Further, the incorporation of indium in Sb-Se system is expected to make it more suitable for reversible optical recording having less erase time [13].…”
Section: Introductionmentioning
confidence: 99%